Anticoagulant activity of black snake (Elapidae: Pseudechis) venoms: Mechanisms, potency, and antivenom efficacy. (15th September 2020) - Zdenek, Christina N.; Youngman, Nicholas J.; Hay, Chris; Dobson, James; Dunstan, Nathan; Allen, Luke; Milanovic, Leontina; Fry, Bryan G.
Highlights: Pseudechis (Black snake) venoms were shown to be potently anticoagulant. Inhibition of FVa was shown to be the primary mechanism. Antivenom was effective except for P. colletti . Varespladib neutralised P. colletti toxicity. Abstract: Venoms from Pseudechis species (Australian black snakes) within the Elapidae family are rich in anticoagulant PLA2 toxins, with the exception of one species ( P. porphyriacus ) that possesses procoagulant mutated forms of the clotting enzyme Factor Xa. Previously the mechanism of action of the PLA2 toxins' anticoagulant toxicity was said to be due to inhibition of Factor Xa, but this statement was evidence free. We conducted a series of anticoagulation assays to elucidate the mechanism of anticoagulant action produced by P. australis venom. Our results revealed that, rather than targeting FXa, the PLA2 toxins inhibited the prothrombinase complex, with FVa—alone or as part of the prothrombinase complex—as the primary target; but with significant thrombin inhibition also noted. In contrast, FXa, and other factors inhibited only to a lesser degree were minor targets. We quantified coagulotoxic effects upon human plasma caused by all nine anticoagulant Pseudechis species, including nine localities of P. australis across Australia, and found similar anticoagulant potency across all Pseudechis species, with greater potency in P. australis and the undescribed Pseudechis species in the NT. In addition, the northern localities and eastern of P. australis were significantly more potent than the central, western, and southern localities. All anticoagulant venoms responded well to Black Snake Antivenom, except P. colletti which was poorly neutralised by Black Snake Antivenom and also Tiger Snake Antivenom (the prescribed antivenom for this species). However, we found LY315920 (trade name: Varespladib), a small molecule inhibitor of PLA2 proteins, exhibited strong potency against P. colletti venom. Thus, Varespladib may be a clinically viable treatment for anticoagulant toxicity exerted by this species that is not neutralised by available antivenoms. Our results provide insights into coagulotoxic venom function, and suggest future in vivo work be conducted to progress the development of a cheaper, first-line treatment option to treat PLA2 -rich snake venoms globally.